THE AGRONOMIC CHARACTER AND POTENTIAL YIELD OF 17’S GENOTYPE OF MAIZE - Shafri Yuranto; Basuki Basuki; Lagiman Lagiman (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2018)
Maize (Zea mays L.) is one of crops that source of carbohydrate than rice. The maize production needs to production goal. The problems is traditional variety haved low yield. This study aims to determine the agronomic character and potential yield of several hybrids maize.. The research method used was randomized completely block design was repeated 3 times. The treatment factor namely hybrid maize genotype. The data obtained were analyzed in theirs diversities by using variace at 5 % level, if there were significant difference, continued by using the least significant increase at 5% level to compared of variety tester. The results shows that hybrid maize genotypes, G2KPW-43, G2KPW-45, and G2KPW-48 haved superiorities in agronomic character and higher potential yield.Key words: genotypes, potential yield, maize